Pengaruh Daya Motor Bensin Terhadap Kapasitas Produksi Mesin Pemipil Jagung - Nasmi Herlina Sari; Nurhasanah Nurhasanah (Universitas Muhammadiyah Sidoarjo, 2018)
The demand for corn kernels is increasing in developing countries. This study focuses to investigated the effect of power engine on the production capacity of corn sheller machine. The power of engine has been varied i.e 4 HP, 5,5 HP and 8 HP. The methods of this research using by empirisly calculated. The results shows that the maximum production capacity obtained on power engine at 8 HP, 5,5 HP and 4 HP are 14 kg/minutes, 10 kg/min, and 7 kg/min, respectively. The conclusion of this research is the production capacity of corn sheller machine affected by power engine, shaft diameter, pegs length, bearing number and spin sheller.